DRUG UTILIZATION STUDY AMONG GERIATRIC PATIENTS IN A TERTIARY CARE TEACHING HOSPITAL IN SOUTH INDIA - ARSHAD, MOHAMMAD; FAYAZUDDIN, MOHD; MUDIUM, RAGHUNANDAN; CHAVAN, VASANT R (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objective of our study is to evaluate the drug utilization pattern among geriatric patients in a tertiary care teaching hospital in South India and analyze the prescription pattern. Methods: Retrospective medical record analysis was performed for indoor cases of the geriatric patients (aged ≥65 years) admitted in medicine wards of Raichur Institute of Medical Sciences teaching hospital, Raichur, from June 2015 to May 2016. They were analyzed for demo graphics, disease pattern by system involved, disease diagnosed, comorbidity pattern, most commonly prescribed drugs, distribution of drugs according to their therapeutic class, evaluation of polypharmacy, route of administration, fixed-dose combinations, and the World Health Organization core prescribing indicators. Results: A total of 400 prescriptions of geriatrics patients admitted in inpatient medicine department were randomly selected and all the required data for the study were collected and evaluated. The majority of patients were found to be in the age group of 65–70 years (70.25%). It was noticed that females (51.75%) were more compared to males (48.25%). The drugs prescribed were analyzed. Ranitidine, ceftriaxone, theophylline, and salbutamol were prescribed to majority of the patients in this study group. The average number of drugs per prescription was 7.42; drugs prescribed by generic name were 33.62%. Among the drugs prescribed, 88.69% were from the National List of Essential Medicines. Total encounters having inject table preparations were 100% and total encounters having antibiotic prescribed were 91%. The prevalence of cardiovascular disorders (32.5%) was high followed by respiratory disorders (32.25%). Conclusion: This study provides insight into the patterns of drug use in our tertiary care hospital on geriatric patients as well as various diseases prevalent among geriatric patients. Widespread polypharmacy, high use of antibiotics and injections, and lack of generic prescribing are some concerns that need to be addressed to promote rational usage of drugs.